The buildings of the plural plural and the ultimate plural and its connotations in the Arabic illiteracy of Shanfari - Hussein Omar Darawcha (Journal of Science and Knowledge Horizons, 2022)
The research studies the structures of the plural plural and the ultimate plural and its implications in the illiteracy of the Arab Shanfari, by talking about the structures of plural plural scalar and the phonological form and clarifying their implications in the context of the llamaic, revealing the plural forms contained in the text of Shanfari's poem and determining their connotations in the context of poetic expression, and classifying The foregoing is according to the standard and phonological morphological structures, and the research followed the descriptive approach based on induction and analysis, and then the conclusion of the research, which includes the results, recommendations, and an index of sources and references